Isomorphism of multiplicative and additive stochastic semigroups of almost linear operators with conditions of continuity - Laytambur , K. N. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
We prove a one-to-one correspondence between sets of multiplicative and additive discontinuous evolutionary systems of strong almost linear operators having a bounded variation.